Expression of genes regulating cell division in porcine follicular granulosa cells - Kulus, Jakub; Kranc, Wiesława; Kulus, Magdalena; Dzięgiel, Piotr; Bukowska, Dorota; Mozdziak, Paul; Kempisty, Bartosz; Antosik, Paweł (Cell division, 2023)
BACKGROUND: Cell cycle regulation influences the proliferation of granulosa cells and affects many processes related to ovarian folliclular growth and ovulation. Abnormal regulation of the cell cycle can lead to many diseases within the ovary. The aim of this study was to describe the expression profile of genes within granulosa cells, which are related to the formation of the cytoskeleton, organization of cell organelles inside the cell, and regulation of cell division. Established in vitro primary cultures from porcine ovarian follicle granulosa cells were maintained for 48, 96, 144 h and evaluated via microarray expression analysis. RESULTS: Analyzed genes were assigned to 12 gene ontology groups "actin cytoskeleton organization", "actin filament organization", "actin filament-based process", "cell-matrix adhesion", "cell-substrate adhesion", "chromosome segregation", "chromosome separation", "cytoskeleton organization", "DNA integrity checkpoint", "DNA replication initiation", "organelle fision", "organelle organization". Among the genes with significantly changed expression, those whose role in processes within the ovary are selected for consideration. Genes with increased expression include (ITGA11, CNN1, CCl2, TPM2, ACTN1, VCAM-1, COL3A1, GSN, FRMD6, PLK2). Genes with reduced expression inlcude (KIF14, TACC3, ESPL1, CDC45, TTK, CDC20, CDK1, FBXO5, NEK2-NIMA, CCNE2). For the results obtained by microarray expressions, quantitative validation by RT-qPCR was performed. CONCLUSIONS: The results indicated expression profile of genes, which can be considered as new molecular markers of cellular processes involved in signaling, cell structure organization. The expression profile of selected genes brings new insight into regulation of physiological processes in porcine follicular granulosa cells during primary in vitro culture.
Keywords: Cell cycle; Transcriptomics; Cellular signaling; Gene expression profile; Follicular granulosa cells; Cytoskeleton organization